Clinical benefit of surveillance after resection of pancreatic ductal adenocarcinoma: A systematic review and meta-analysis. Issue 9 (September 2021) - Halle-Smith, James M.; Hall, Lewis; Daamen, Lois A.; Hodson, James; Pande, Rupaly; Young, Alastair; Jamieson, Nigel B.; Lamarca, Angela; van Santvoort, Hjalmar C.; Molenaar, Izaak Quintus; Valle, Juan W.; Roberts, Keith J.
Abstract: Background: The value of routine surveillance after resection of pancreatic ductal adenocarcinoma (PDAC) is unclear, and expert guidelines offer conflicting recommendations. This study is a systematic review of evidence for surveillance programs. Methods: A systematic review of studies evaluating different surveillance methods was undertaken. A meta-analysis was performed for those studies reporting rates of asymptomatic recurrence, treatment of recurrence and overall survival, according to different surveillance methods. Results: Ten studies were included in the literature review, with five studies appropriate for meta-analysis (1596 patients). Patients within active surveillance programs were more likely to have recurrence detected at an asymptomatic stage (Pooled Rate: 49.3% vs. 19.1%, p = 0.043). Within studies reporting these outcomes, patients with asymptomatic recurrence were more likely to receive treatment for recurrence (Odds Ratio 3.49; 95% CI: 1.73–7.07; p < 0.001) and had longer overall survival (Mean Difference: 9.5 months; 95% CI: 4.1–14.8; p < 0.001) than those with symptoms at time of recurrence. Discussion: Routine surveillance after surgery for PDAC appears to detect more patients at an asymptomatic stage. Data from these non-randomised trials also suggest that treatment rates and survival may be superior in patients were recurrence is detected when asymptomatic. As such, these data suggest that routine surveillance may improve patient outcomes, although an appropriately conducted trial would be required to address concerns that various sources of bias may be affecting these results.